Plasma microRNAs Predict Chemoresistance in Patients With Metastatic Breast Cancer. (19th July 2019) - Shao, Bin; Wang, Xiaoxia; Zhang, Lei; Li, Deyu; Liu, Xiaoran; Song, Guohong; Cao, Huiqing; Zhu, Jun; Li, Huiping
Background: MicroRNAs contribute to chemotherapy response in different types of cancer. We hypothesized that plasma miRNAs are potentially associated with chemotherapy response in patients with metastatic breast cancer. Patients and Methods: Fourteen candidate microRNAs were chosen from the literature, and their plasma levels were measured by quantitative polymerase chain reaction (PCR). Forty metastatic breast cancer patients were chosen as the training groups. The potential significant microRNAs were validated in another 103 plasma samples. Results: In the training set, we identified 3 microRNAs (miR-200a, miR-210, and miR-451) as significantly dysregulated miRNAs between sensitive group (partial response (and stable disease) and resistant group (progressive disease). Then, in the validation set, miR-200a (area under the curve = 0.881, sensitivity = 94.1%, specificity = 76.7%) and miR-210 (area under the curve = 0.851, sensitivity = 88.2%, specificity = 72.1%) showed high diagnostic accuracy for distinguishing sensitive group from resistant group. Furthermore, the plasma level of miR-200a was significantly associated with the stage in surgery ( P = .035), and the high level of miR-210 expression was associated with internal organ metastasis (liver, lung, and brain; P = .024). Conclusions: Plasma miR-200a and miR-210 could be effective biomarkers for the prediction of chemotherapy resistance in metastatic breast cancer patients.